(untitled) (Mustansiria Dental Journal, 2018)
Background: Strontium (Sr) is an alkaline earth trace metal cation that has a high affinity for hydroxyapatite. This study aimed to examine the histological effect of locally injected strontium (Sr) on prevention and repair of induced root resorption of rat molar subjected to orthodontic tooth movement. Materials and Methods: Eighteen ten-week- old male Wister rats were randomly divided into two groups of nine animals for two experiments. In both experiments; uniform standardized expansive springs were used to move maxillary first molars buccally for three weeks and then removed. In experiment No.1, at the time of spring placement, 0.25 ml of the strontium chloride solution at a concentration 240 mg/ml was injected at the sub-periosteum of the buccal side of the maxillary left first molar which was the experimental side. On other hand, 0.25 ml of distilled water was injected at the sub-periosteum of the buccal side of the right maxillary first molar which was the control side. The injections repeated every other day for three weeks whereas in experiment 2 it was begun at the day of spring removal and repeated every other day for another three weeks. After that the animals were scarified humanly and biopsies were taken for histological examination. Results: In experiment 1 the side injected with strontium showed statistically significant lesser root resorption than control side, while in experiment two the strontium injected side showed significantly more repair. Conclusion: Results of the study suggested that local injection of strontium can inhibit root resorption process and enhance repair.